The Effect of Focal Damage to the Right Medial Posterior Cerebellum on Word and Sentence Comprehension and Production - Sharon Geva; Letitia M. Schneider; Letitia M. Schneider; Sophie Roberts; David W. Green; Cathy J. Price (Frontiers in Human Neuroscience, 2021)
Functional imaging studies of neurologically intact adults have demonstrated that the right posterior cerebellum is activated during verb generation, semantic processing, sentence processing, and verbal fluency. Studies of patients with cerebellar damage converge to show that the cerebellum supports sentence processing and verbal fluency. However, to date there are no patient studies that investigated the specific importance of the right posterior cerebellum in language processing, because: (i) case studies presented patients with lesions affecting the anterior cerebellum (with or without damage to the posterior cerebellum), and (ii) group studies combined patients with lesions to different cerebellar regions, without specifically reporting the effects of right posterior cerebellar damage. Here we investigated whether damage to the right posterior cerebellum is critical for sentence processing and verbal fluency in four patients with focal stroke damage to different parts of the right posterior cerebellum (all involving Crus II, and lobules VII and VIII). We examined detailed lesion location by going beyond common anatomical definitions of cerebellar anatomy (i.e., according to lobules or vascular territory), and employed a recently proposed functional parcellation of the cerebellum. All four patients experienced language difficulties that persisted for at least a month after stroke but three performed in the normal range within a year. In contrast, one patient with more damage to lobule IX than the other patients had profound long-lasting impairments in the comprehension and repetition of sentences, and the production of spoken sentences during picture description. Spoken and written word comprehension and visual recognition memory were also impaired, however, verbal fluency was within the normal range, together with object naming, visual perception and verbal short-term memory. This is the first study to show that focal damage to the right posterior cerebellum leads to language difficulties after stroke; and that processing impairments persisted in the case with most damage to lobule IX. We discuss these results in relation to current theories of cerebellar contribution to language processing. Overall, our study highlights the need for longitudinal studies of language function in patients with focal damage to different cerebellar regions, with functional imaging to understand the mechanisms that support recovery.